Analisis Profil Pelajar Pancasila Sub-Elemen Disiplin Diri Dalam Ekstrakurikuler Pramuka Pada Siswa Kelas IV - Riska Ayu Andini; Aditya Dyah Puspitasari (JURNAL RISET RUMPUN ILMU PENDIDIKAN, 2024)
The purpose of this research is to determine the profile of Pancasila students, the sub-element of self-discipline in Scout extracurriculars for grade 4 students. This research used descriptive qualitative methods. The subjects used were grade 4 students. The sampling used non-probability sampling. The research sample was 3 students, with the consideration that the students’ scout grades were good and sufficient. Data collection using observation sheets, interviews and documentation. The results of the research showed that Students had a self-disciplined attitude in the process of Scout extracurricular activities, Students were able to organize themselves independently regarding the data before the Scout activity started, Students wore scout uniforms carrying sticks, ropes according to the needs of the learning process, students were able to organize themselves to be orderly when scouting activities take place, Students also carry out activities or tasks that have been agreed upon independently, Students are able to pray according to the agreed habits, follow instructions from their senior mentor, carry out the tasks given independently to their part during the task of making scouts in groups. For students in the sufficient category, the appear in all activities except for the practice of making a stretcher which is still needed.